Proses Peruraian Anaerobik Palm Oil Mill Effluent dengan Media Zeolit Termodifikasi - Melly Mellyanawaty; Firda Mahira Alfiata Chusna; Estin Nofiyanti (Departemen Teknik Kimia Fakultas Teknik Universitas Gadjah Mada, 2019)
A B S T R A C TThis work evaluated the effect of modified zeolite as microbial immobilization medium in anaerobic digestion of palm oil mill effluent (POME). The affinity of microorganisms to attach and grow on the media surface could be increased by the addition of micro-nutrient into the media. The effect of micro-nutrient addition was studied in 1000 mL Erlenmeyer flask as batch reactors. Experiments were conducted for 30 days. The concentration of soluble chemical oxygen demand (COD) in substrate was 8000 mg/L. Zeolite was impregnated with nickel (Ni) and zinc (Zn) at individual concentration of 2.7x10-3 mg Ni/g zeolite and 3.5x10‑3 mg Zn/g zeolite. The influence of each modified zeolite was determined by periodic measurement of sCOD, volatile fatty acid (VFA), pH, and biogas production. Cumulative biogas productions in this study were 252.44; 172.13; 57.70 ml from Ni-modified, Zn-modified and natural zeolites, respectively. The highest sCOD removal was obtained in reactor with Zn-modified zeolite with 38.22% removal, followed by 33.96% with Ni-modified zeolite, and 27.87% removal with natural zeolite.Keywords: anaerobic digestion; biogas; methane; palm oil mill effluent; zeoliteA B S T R A KPenelitian ini mengevaluasi pengaruh zeolit yang dimodifikasi sebagai media imobilisasi mikroorganisme pada proses anaerobik limbah palm oil mill effluent (POME). Afinitas mikroorganisme untuk melekat dan tumbuh di permukaan dapat meningkat dengan impregnasi mikronutrien pada media. Efek penambahan mikronutrien dipelajari dengan labu Erlenmeyer 1000 mL sebagai reaktor batch. Experimen dijalankan selama 30 hari. Konsentrasi soluble chemical oxygen demand (sCOD) substrat yang digunakan adalah 8000 mg/L. Zeolit terimpregnasi Ni dan Zn yang digunakan memiliki kadar 2,7 x10-3 mg Ni/g zeolit dan 3,5x10-3 mg Zn/g zeolit. Pengaruh setiap zeolit yang dimodifikasi dievaluasi dengan mengukur konsentrasi sCOD, volatile fatty acid (VFA), pH, dan produksi biogas secara periodik. Akumulasi biogas penelitian ini sebesar 252,44; 172,13; 57,70 ml berturut-turut untuk zeolit modifikasi Ni, zeolit modifikasi Zn dan zeolit alam. Penurunan sCOD terbaik dihasilkan oleh zeolit termodifikasi Zn dengan nilai 38,22%, selanjutnya diikuti oleh zeolit termodifikasi Ni dan zeolit alam dengan nilai 33,96% dan 27,87%.Kata kunci: anaerobic digestion; biogas; metana; palm oil mill effluent; zeolit